Fatores associados à lesão por pressão em pacientes hospitalizados: estudo caso-controle. - Moreira, Marcela Gama Santana (2019)
Pressure injury (PI) is a complex and multifactorial phenomenon caused by intrinsic and extrinsic factors. Knowledge of this factors and the recognition of patients at risk by the multidisciplinary team, especially nursing, are fundamental for the planning of individualized and effective preventive actions. The present study aimed to feature the clinical and laboratory profile of patients affected by PI during hospitalization, identify the factors associated with its development and verify whether PI is a factor associated with death among these patients. It is a retrospective case-control study conducted in a private hospital in Aracaju city, Sergipe, with a sample of 285 patients, being 95 cases and 190 controls. The case group consisted of patients who developed PI from June 2017 to June 2018, and the control group by patients without PI during hospitalization. Data collection took place from September 2018 to March 2019. Patients in the case group were identified through PI incidence reports, and those in the control group by the hospital’s monthly skin committee database. Patients older than 18 were included. The exclusion criterion in the case group was patients only presenting injury caused by medical device, whereas in the control group it was patients previously affected by PI and with hospitalization time being less than five days or more than a year. Sociodemographic, clinical and laboratory data of the participants were collected through in electronical medical records and analyzed by the R Core Team 2019 software. Univariate analysis of all study variables was performed, followed by multivariate analysis with simple and early logistic regression to identify the associated factors and the raw and adjusted odds ratio (OR). Variables with p<0,05 were considered significant. The results showed the gluteal region as the most affected by pressure injuries and the “deep tissue” stage as the most frequent. Attributes of the patients with these wounds were advanced age, high risk Braden and need for hemodynamic watch. 54,7% of the patients having PI passed away. Factors related to the development of PI were: anemia (OR 2,61; P=0,022), thrombocytopenia (OR 2,54; P=0,047), high platelet count (OR 5,96; P= 0,014), need for ventilatory support (OR 3,31; P= 0,002) and hemodialysis (OR 2,90; P= 0,013), malnutrition (OR 2,18; P=0,042) and Braden scale score (OR 0,68; P< 0,001). Presence of PI was a factor associated with death of hospitalized patients. The results of this study point to the strengthening of multidisciplinary action in prevention of PI in order to implement effective strategies.